Desain Mesin Hot Press Untuk Pembuatan Papan Komposit Dari Serat Batang Kelapa Sawit - Perdana, Regi Octa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Oil palm trunk has a low mechanical properties compared to other woods, so that the oil palm trunks can be used as building materials and furniture, should be improoved in the quality of oil palm trunk by making a composite board. To get a hot press machine to produce a composite board, it is necessary to design the hot press machine that includes the design elements of the machines used and the analysis of the structural strength of the static loading and thermal loading using finite element method software. The conclusion, among others: (1) The design of the power screw is the screw thread diameter 30 mm with pitch 3,5 mm. From design of roller chain, the chain number is 06 B with load on the chain amounted 205,84 N. (2) the results of the simulation at temperature 27oC, Von-Misses stress is 154,6 MPa, the deformation 0,31357 mm and a safety factor 4,2. For temperature 200oC, Von-Misses stress is 442,36 MPa, the deformation 0,70437 mm as well as the safety factor for the engine hot press amounting to 1,48.Keyword : Oil Palm Trunk, Composite board, Hot Press Machine, Finite Elemen Method, Temperature changes, Static and Thermal Load.